FUNGSI DINAS PENDIDIKAN DALAM PEMBINAAN DAN PELATIHAN GURU DI KOTA PEKANBARU (STUDI KASUS TENTANG KUALITAS GURU PENDIDIKAN DASAR) - ", Khairina; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Functions of the Office of education in coaching and training teachers in the city of Pekanbaru (case study of the quality of teachers of basic education). In this study the author based on the theory of Subekhi A. & Jauhar (2013: 127) about what the functions of the Organization and the theory of Musfah (2011: 12-13) about the factors which affected it. That there are several stages that must be known to run a function, namely: planning, management, reporting, and oversight. By doing this education service function in doing coaching and training can be organized properly and achieve the desired objectives for the improvement of the quality of basic education teachers so effective and good learning process. The results of the research function of the Office of education in coaching and training teachers in the city of Pekanbaru has done quite well but not yet fully reached the goal and not the maximum.Keywords: primary education, functional organization, coaching and training.